Cooperative Learning: Strategi Pengembangan Inovasi Pendidikan Di Indonesia - Meidawati Suswandari (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2019)
This study aims to critically analyze Education innovation in Indonesia through twenty-four precise strategies of Education strategy. This type of research is library research. Data collection by identifying discourses from books, papers or articles, journals, newspapers, internet (web), or other information related to education. Data analysis uses descriptive analysis, content analysis, and scientifically critical analysis. The results of the study show that Educational innovation in Indonesia can apply twenty-four Educational strategies which include Personalization, Multi-Age Classes, Small Community Learning, Peer Group Learning, Small Group Learning Communities with other groups, Multidisciplinary Curriculum with Block Scheduling, Cooperative Learning, Cooperative Learning, Based Learning Projects, Instruction Associates, Teaching Teams, Community Service Learning, Looping Partnerships, Businesses for Assessments, Resources and Funding, Global Connections, Laptops and Wireless Technology for Learning Wherever and Anytime, Parent Engagement, Students Showing Shows, Life Skills Curriculum (Non- Academic), Meaningful Career Counseling, Social / Emotional Counseling, Open Learning, Education to serve Student Needs, Portfolio-Based Assessment and the New Paradigm of School Buildings.